Development and evaluation of a user-centric database of drug information and images at Warinchamrab Hospital. - Supapaan, Teeraporn Sadira; Somsorn, Surat; Saensupha, Natthida; Songmuang, Thanatcha; Songmuang, Ananya; Jaturapattarawong, Aporn; Sripa, Saksit; Jinatongthai, Peerawat; Napaporn, Jintana (Pharmacy Practice (1886-3655))
Background: The COVID-19 pandemic situation has emphasized the need for accessible drug information in primary healthcare, mainly owing to limited hospital visits. Patients with chronic illnesses experience difficulties obtaining regular medications, and this problem is worsened by the unavailability of drugs and prescriptions shared via mail. Hospitals are actively working to develop user-friendly drug information databases to enhance medication management in their facilities. Objective: In this study, we aimed to establish a hospital database for improved medication management that can serve the purposes of both healthcare providers and patients. Methods: This study comprised two parts: 1) the development of drug information and image database websites, involving the survey of user needs, designing the website, compiling drug lists and related data, recording images of tablets and capsules, creating the website, and testing its functionality; 2) the evaluation of the user interface satisfaction with the drug database website. Results: Part 1: A database was developed using comprehensive details of 710 hospital drugs, including tablets, capsules, and liquids. Images of the medications were integrated to enable users to search for drug information. Three types of reports are generated to fulfill the user requirements. Part 2: Thirty-one pharmacy staff members evaluated satisfaction across four aspects; high mean scores (± standard deviations) for attitude and intention to use (4.33 ± 0.067), searching and display (4.32 ± 0.000), display results (4.30 ± 0.042), and structure and operation (4.12 ± 0.097) indicated high user satisfaction. Conclusion: A comprehensive hospital-based drug database has been developed. This database is associated with a user-friendly website with robust search capabilities. The three report types cater to diverse user requirements. Further analyses of this database revealed high user interface satisfaction across various aspects, particularly in terms of clarity, ease of use, search efficiency, and image quality.